Disaster Mitigation Program By Radio Nebula FM Palu Central Sulawesi - Nur Rahmah Sintya; Achmad Herman; Kudratullah Kudratullah (Kanal: Jurnal Ilmu Komunikasi, 2022)
This study aims to determine the production process of disaster mitigation education programs by Radio Nebula FM and the continuity of disaster mitigation education programs by Radio Nebula FM. This research is descriptive qualitative with an action research approach. The data collection techniques are observation techniques, interviews, and documentation studies of four informants who have been selected through purposive sampling techniques. The informants who have been selected are employees of PT Radio Nebula Nada, actively involved in the preparation of the 101 mitigation program, and have hosted the 101 mitigation broadcast program.The results showed that the production process of the 101 Radio Nebula mitigation education program had three stages, namely the pre-production, production, and post-production stages. The stages in pre-production consist of discussing ideas and concepts, determining the format of the program, finding topics you want to review while on air and off-air, preparing scripts or scripts, choosing music, and preparing an operational budget. Then the production stage is to maximize the Term of Reference (TOR), take vocals for advertisements, on air for talk shows and news programs as well as outpouring programs (vent) for disaster survivors. Lastly in the post-production stage is the evaluation of the 101 mitigation program by the entire Nebula FM Radio production team. Regarding the continuity of the program, the 101 mitigation program was continued with reduced intensity and the name of the program was changed to Sulteng Round-Up.